2012
DOI: 10.3390/ijms13055528
|View full text |Cite
|
Sign up to set email alerts
|

Early Fixation of Cobalt-Chromium Based Alloy Surgical Implants to Bone Using a Tissue-engineering Approach

Abstract: To establish the methods of demonstrating early fixation of metal implants to bone, one side of a Cobalt-Chromium (CoCr) based alloy implant surface was seeded with rabbit marrow mesenchymal cells and the other side was left unseeded. The mesenchymal cells were further cultured in the presence of ascorbic acid, β-glycerophosphate and dexamethasone, resulting in the appearance of osteoblasts and bone matrix on the implant surface. Thus, we succeeded in generating tissue-engineered bone on one side of the CoCr i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Briefly, primary bone marrow cells aspirated from the humeral heads of rabbits were cultured in regular medium consisting of Earle's Minimal Essential Medium (Nacalai Tesque, Kyoto, Japan) with 15% fetal bovine serum (JRH Bioscience, Lenexa, KS) and antibiotics (100 U/mL penicillin and 100  μ g/mL streptomycin; Nacalai Tesque) for 2 weeks [18, 19]. After reaching confluence, the cells were released and seeded at 1 × 10 4 cells/cm 2 onto 10 cm culture dishes (Falcon, BD Biosciences, Franklin Lakes, NJ) in the above medium supplemented with 10 nM dexamethasone (Dex; Sigma, St. Louis, MO) and 82  μ g/mL ascorbic acid phosphate (Asap; L-ascorbic acid phosphate magnesium salt n -hydrate; Wako Pure Chemical Industrials, Kyoto, Japan) for 14 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, primary bone marrow cells aspirated from the humeral heads of rabbits were cultured in regular medium consisting of Earle's Minimal Essential Medium (Nacalai Tesque, Kyoto, Japan) with 15% fetal bovine serum (JRH Bioscience, Lenexa, KS) and antibiotics (100 U/mL penicillin and 100  μ g/mL streptomycin; Nacalai Tesque) for 2 weeks [18, 19]. After reaching confluence, the cells were released and seeded at 1 × 10 4 cells/cm 2 onto 10 cm culture dishes (Falcon, BD Biosciences, Franklin Lakes, NJ) in the above medium supplemented with 10 nM dexamethasone (Dex; Sigma, St. Louis, MO) and 82  μ g/mL ascorbic acid phosphate (Asap; L-ascorbic acid phosphate magnesium salt n -hydrate; Wako Pure Chemical Industrials, Kyoto, Japan) for 14 days.…”
Section: Methodsmentioning
confidence: 99%
“…The proximal tibiae were harvested 3 weeks after the operation [11, 19]. The tibiae for histological evaluation were fixed in 10% neutral buffered formalin, decalcified in EDTA solution, and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transplanted MSCs significantly improved the implant integration evident by increased bone formation and enhanced bone/implant contact area. Ogawa et al seeded rabbit MSCs on the surface of CoCr implant and differentiated them into bone forming osteoblasts in vitro prior to implantation in vivo . Implant integration to bone was significantly enhanced as evaluated by histomorphometry and mechanical testing of the bone implant interface.…”
Section: Msc‐targeted Treatment Options Of Aseptic Looseningmentioning
confidence: 99%
“…However, it has been demonstrated that both osteoblast activity and blood vessel formation are improved by the addition of this platelet concentrate, possibly leading to better bone quality, attributing these characteristics to the early release of GFs from the platelet granules during platelet interactions with agents such as collagen or thrombin within the first days after supply. The advantage is that the autologous nature of PRP causes no risk of allergies or tissue versus host reactions [98] in contrast with other osteoinductive agents. Additionally, it has been demonstrated that each of the GFs contained in the platelet granules may produce different positive effects on new bone formation [99].…”
Section: Heat Treatmentmentioning
confidence: 99%